Closing the achievement gap: challenges and opportunities - O'Toole, Barbara; Skinner, Barbara (Marino Institute of Education and University of Ulster, 2018)
This e-publication is based on two seminars on teaching English as an Additional Language (EAL), which were held at Ulster University (UU) in Coleraine and at Marino Institute of Education (MIE) in Dublin in 2017. The seminars were entitled Minority language pupils and the curriculum – closing the achievement gap and were supported by funding from the Standing Conference on Teacher Education North and South (SCoTENS) along with funding from UU and MIE.
Keywords: Education; EAL; Primary Education; Minority language pupils; Inclusion; Teacher Education